2021
DOI: 10.1128/mbio.00390-21
|View full text |Cite
|
Sign up to set email alerts
|

Bradyrhizobium diazoefficiens Requires Chemical Chaperones To Cope with Osmotic Stress during Soybean Infection

Abstract: When engaging in symbiosis with legume hosts, rhizobia are confronted with environmental changes, including nutrient availability and stress exposure. Genetic circuits allow responding to these environmental stimuli to optimize physiological adaptations during the switch from the free-living to the symbiotic life style. A pivotal regulatory system of the nitrogen-fixing soybean endosymbiont Bradyrhizobium diazoefficiens for efficient symbiosis is the general stress response (GSR), which relies on the alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 79 publications
(106 reference statements)
0
12
0
Order By: Relevance
“…We found that the mutation resulted in an increased transcription of four genes, while it reduced the expression of three genes. An increased transcription of otsB was obtained in the ∆rpoE2 strain, indicating that RpoE2-mediated GSR in E. aridi involves the T6P pathway, as shown in S. meliloti [45] or in B. diazoefficiens [74]. We also found that for rsiA1, the anti-sigma factor that is located upstream of and overlaps the 5 end of the rpoE2 gene forming an operon was less expressed in the mutant, which suggests, again, that, as shown in other alphaproteobacteria [65], rpoE2 is autoregulated in E. aridi.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…We found that the mutation resulted in an increased transcription of four genes, while it reduced the expression of three genes. An increased transcription of otsB was obtained in the ∆rpoE2 strain, indicating that RpoE2-mediated GSR in E. aridi involves the T6P pathway, as shown in S. meliloti [45] or in B. diazoefficiens [74]. We also found that for rsiA1, the anti-sigma factor that is located upstream of and overlaps the 5 end of the rpoE2 gene forming an operon was less expressed in the mutant, which suggests, again, that, as shown in other alphaproteobacteria [65], rpoE2 is autoregulated in E. aridi.…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, recent work on B. diazoefficiens showed that ecfG mutation resulted in increased sensitivity to various stresses including hyperosmotic and ionic stresses [74]. More interestingly, in both Bradyrhzobium diazoefficiens and Sinorhizobium meliloti, a rpoE2 mutation was shown to repress trehalose 6 Phosphate pathway, which was involved in hyperosmotic stresses' tolerance [45] and was sufficient to impair early symbiotic development in the more sensitive B. diazoefficiens species [74], further supporting that trehalose is a key compatible solute for Bradyrhizobium stress adaptation and nodulation, as shown in B. japonicum [46]. The absence of a symbiotic phenotype observed in the rpoE2 mutant of S. meliloti may result from a high tolerance to hyperosmotic stress in this species as compared to the Bradyrhizobium species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This size is smaller than the Bradyrhizobium nodules in general, which have a length ranging from 5-10 mm for Indigofera (Bünger et al 2021). Nodulations in other plants such as shrubby sophora (Sophora flavescens) and soybean (Glycine max) are smaller, about 1-3 mm long (Ledermann et al 2021;Liu et al 2018). This size is also influenced by the type and age of the plant, where Indigofera has a relatively long life.…”
Section: Resultsmentioning
confidence: 89%
“…Biosynthesis of compatible solutes such as trehalose or N -acetylglutaminylglutamine amide (NAGGN) contributes to adaptation to high osmolarity environments in Sinorhizobium ( Flechard et al , 2010 ; Sagot et al , 2010 ), Rhizobium ( McIntyre et al , 2007 ), or Bradyrhizobium ( Ledermann et al , 2021 a ). Whilst trehalose biosynthesis is needed in Bradyrhizobium for growth in infection threads ( Ledermann et al, 2018 , 2021 a ), no mutants in compatible solute biosynthesis with an effect on bacteroids have so far been reported. This raises the question of how rhizobia adapt to the osmotic conditions in nodules.…”
mentioning
confidence: 99%